Phenotypic Plasticity in Gut Length in the Planktivorous Filter-Feeding Silver Carp (Hypophthalmichthys molitrix) - Zhixin Ke; Xie Ping; Longgen Guo (The Scientific World Journal)
Phenotypic plasticity widely exists in the external morphology of animals as well as the internal traits of organs. In the present study, we studied the gut length plasticity of planktivorous filter-feeding silver carp under different food resources in large-net cage experiments in Meiliang Bay of Lake Taihu in 2004 and 2005. There was a significant difference in stocking density between these 2 years. Under a low stocking density and abundant food resources, silver carp increased their energy intake by feeding on more zooplankton. Meanwhile, silver carp adjusted their gut length to match the digestive requirements of food when exposed to different food resources. In the main growth seasons (from April to October), silver carp significantly increased their relative gut length when feeding on more phytoplankton in 2005 (p < 0.01, 9.23 ± 1.80 in 2004 and 10.77 ± 2.05 in 2005, respectively). There was a nearly significant negative correlation between zooplankton proportion in the diet and the relative gut length when silver carp were stocked in a high density (p = 0.112). It appears that silver carp might have evolved plasticity to change their gut length rapidly to facilitate efficient utilization of food resources. Such resource polymorphisms in the gut may be a good indication of temporal adaptation to resource conditions. Our work provided field evidence for understanding the functional basis of resource polymorphisms and the evolution of phenotypic plasticity in planktivorous filter-feeding fish.